223k views
5 votes
Please at least help me cause I have no idea

Solve for v2

a \: ave = (v2 - v1)/(t2 - t1)


1 Answer

0 votes

Answer:

Solving the given formula for v2 gives us:


a(t_2-t_1)+v_1 = v_2

Explanation:

Solving an equation for a particular variable means that the variable has to be isolated on one side of the equation.

Given equation is:


a = (v_2-v_1)/(t_2-t_1)

Multiplying both sides by t2-t1


(t_2-t_1) . a = (v_2-v_1)/(t_2-t_1) . (t_2-t_1)\\a(t_2-t_1) = v_2-v_1

Adding v1 to both sides of the equation


a(t_2-t_1)+v_1 = v_2-v_1+v_1\\a(t_2-t_1)+v_1 = v_2

Hence,

Solving the given formula for v2 gives us:


a(t_2-t_1)+v_1 = v_2

User Neri
by
5.5k points